2001
DOI: 10.1108/09526860110386474
|View full text |Cite
|
Sign up to set email alerts
|

“A little encouragement”: health services and domestic violence

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(92 citation statements)
references
References 5 publications
5
84
0
1
Order By: Relevance
“…33 Research has shown that the attitude of caregivers is very important in helping women to disclose abuse and tell their stories. 34 Third, AIAN women seek help through both Western-centered establishments and traditional Native interventions. It is critical, therefore, that culturally specific services are offered to women in conjunction with standard mental health services, or as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…33 Research has shown that the attitude of caregivers is very important in helping women to disclose abuse and tell their stories. 34 Third, AIAN women seek help through both Western-centered establishments and traditional Native interventions. It is critical, therefore, that culturally specific services are offered to women in conjunction with standard mental health services, or as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers relating to the health care providers' sense of powerlessness are often categorized as system obstacles and a lack of education about the causes and effects of IPV and successful interventions. The barriers are diverse and include a lack of knowledge about the availability of local resources; lack of time; lack of collegial support; frustration with legal issues, including mandatory reporting; the need for confidentiality; lack of provider continuity; and personal discomfort with the issue of IPV either from a perspective of it being an overwhelming social issue or from a past personal experience with violence 13–16 . Despite the wide publication of the prevalence of IPV in the United States in both lay media and professional journals, health care providers often state that IPV is not present in their patient population or that it is a personal situation that should be kept between the partners 17 .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The second area of health care providers' concerns is related to fear that the woman will experience increased violence if the perpetrator is aware of her acknowledging violence to a health care provider, and a fear of offending and alienating patients 14 . Health care providers also report frustration with patients' lack of disclosure or willingness to discuss violence 13–16 . Although research about barriers to screening has primarily been conducted with physicians, nurses and midwives have identified several of the same concerns for screening as those reported by physicians 16,19 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…In order to promote more systemsbased delivery of care, promoting more collaborative, unified, and cohesive agency-to-agency initiatives, current research proposes that service agencies look outward to advance care inwardly (Bates et al, 2001;Brilliant & Young, 2004;Hyde, 2004;Jackson et al, 2002;Peled, 2000;Skinner & Whyte, 2004). Successful organizations focus on continuous improvement and are more tolerant of changing regulations and ambiguities, while possessing initiatives such as flexibility, accountability, and shared responsibilities (Lawson, 2003;Martin-Castilla, 2002;Panzer et al, 2000;Warshaw, Gugenheim, Moroney, & Barnes, 2003).…”
Section: Resultsmentioning
confidence: 94%
“…Professionals could include facilitating enhanced interagency cooperation, which involves relaxing agency boundaries and encouraging networking (Bates, Hancock, & Peterkin, 2001;Bolman & Deal, 2003). Literature reviewed shows that service agencies are deficient in providing holistic care.…”
Section: Review Of the Literaturementioning
confidence: 99%